Penerapan Hak Hadhanah Pada Anak Yang Belum Mumayyiz Perspektif Mazhab Syafi’i - Muhammad Fiqri (Populer: Jurnal Penelitian Mahasiswa, 2023)
Divorce is an act that is lawful, but hated by Allah SWT. The consequences of divorce between husband and wife are among them hadhanah (child rearing). Each husband and wife fight over who is most entitled to have a role in the hadhanah. In particular, the status of the child is still not mumayyiz, so the mother has an important role in the right to care according to the as-Syafi'i school. This type of research uses library research (library research) which is qualitative analytic in nature. The data analysis technique is by analyzing the opinion of the as-Shafi'i school of thought regarding the right to hadhanah along with its legal analysis. The results of this thesis research are first, hadhanah rights are given to mothers before the age of 7 or 8 years, after that the child is given the right to choose between father and mother as long as the mother has not married another man. Setting the age of 7 or 8 is not the final limit for hadhanah, but it is the right for children to determine who to have hadhin. Second, the analysis of the as-Shafi'i school uses the argument from al-Quran sura at-Tahrim verse 6, which contains the general basis of hadhanah, then sura al-Baqarah verse 233, which contains the role of the mother in caring for her child, such as breastfeeding, caring. So the father's role in this case provides a living for the mother for breastfeeding. Third, the analysis of the opinion of the as-Shafi'i school is very relevant to the current family phenomenon. Where is the function of the father to make a living and the mother is at home. If parenting is given to the father, it is feared that the hadhanah will not be maximized.